Antimicrobial Activity of Mast Cells: Role and Relevance of Extracellular DNA Traps - Möllerherm, Helene; von Köckritz-Blickwede, Maren; Branitzki-Heinemann, Katja (Frontiers in Immunology, 2016)
Mast cells (MCs) have been shown to release their nuclear DNA and subsequently form mast cell extracellular traps (MCETs) comparable to neutrophil extracellular traps, which are able to entrap and kill various microbes. The formation of extracellular traps is associated with the disruption of the nuclear membrane, leads to mixing of nuclear compounds with granule components and causes the death of the cell, a process called ETosis. The question arises why do MCs release MCETs although they are very well known as multifunctional long-living sentinel cells? In the first place, MCs are known to play a role during allergic reactions and certain parasitic infections. Nonetheless, they are also critical components of the early host innate immune response to bacterial and fungal pathogens: MCs contribute to the initiation of the early immune response by recruiting effector cells including neutrophils and macrophages by locally releasing inflammatory mediators such as TNF-α. Moreover, various studies exhibit that MCs are able to eliminate microbes through intracellular as well as extracellular antimicrobial mechanisms including MCET-formation similar to that of professional phagocytes. The actual literature leads to the suggestion that MCET-formation is not the result of passive release of DNA and granule proteins during cellular disintegration, but rather an active and controlled process in response to specific stimulation which contributes to the innate host defense. This review will discuss the different known aspects of the antimicrobial activities of MCs with special focus on MCETs and their role and relevance during infection and inflammation.